2020
DOI: 10.1080/15592294.2020.1834917
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of transcriptome-wide m6A methylome in the anterior capsule of the lens of high myopia patients

Abstract: To assess the m 6 A methylome in the anterior capsule of the lens of high myopia patients. MeRIPseq and RNA-seq were performed to identify differences in the m 6 A methylomes and gene expression between anterior capsule of the lens of simple nuclear cataract patients (N) and nuclear cataract patients with high myopia (G). Expression of m 6 A-related enzymes was confirmed by quantitative real-time-PCR. ALKBH5 was downregulated in G. The observed m 6 A peak was identical to the conserved RRACH gmotif and was mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…The generated data in the present study displayed that a diverse pattern of mRNA methylation have occurred over the testis development. These mRNA m6A sites were mainly concentrated around the CDS and 3′UTRs region (95.28%), in agreement with the distributional characteristics of the mammalian transcriptomes ( Wen et al, 2020 ). Our data showed that although the m6A peaks for each group markedly varied on different chromosomes, they had a highest expressed distribution in chromosome 19 within groups.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The generated data in the present study displayed that a diverse pattern of mRNA methylation have occurred over the testis development. These mRNA m6A sites were mainly concentrated around the CDS and 3′UTRs region (95.28%), in agreement with the distributional characteristics of the mammalian transcriptomes ( Wen et al, 2020 ). Our data showed that although the m6A peaks for each group markedly varied on different chromosomes, they had a highest expressed distribution in chromosome 19 within groups.…”
Section: Discussionsupporting
confidence: 80%
“…In the study, a total of 2,278 unique DMGs were identified among all the pairwise groups. Differential m6A methylation has proved to be responsible for tissue or organ differentiation and development ( Wen et al, 2020 ). Regarding the function and pathway of DMGs, we performed GO and KEGG enrichment analysis for DMGs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found the m 6 A modification level of BMP4 and KCNN2 were consistent with their gene expression. This suggests that changes in the level of m 6 A modification of genes are likely to affect gene expression [38]. At present, many studies have confirmed that YT521-B homology (YTH) and insulin-like growth factor 2 mRNA-binding protein (IGF2BP) domain play a role in mRNA stabilization, translation and degradation by recognizing methylated m 6 A sites on genes [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Using MeRIP‐seq and RNA‐seq, one recent study comprehensively analyzed the transcriptome‐wide m6A methylome and gene expressions of the anterior capsule of the lens in highly myopic patients with nuclear cataract anterior. They found that METTL14 was upregulated whereas METTL3, FTO, ALKBH5, YTHDF1, and YTHDF2 were downregulated, which suggests that m6A methylation was strongly associated with the pathogenic mechanism of high myopia (Wen et al, 2021). Overall, these studies have uncovered the regulatory roles of m6A modifications in aging‐related cataracts.…”
Section: Rna Modifications In Aging‐related Cataractsmentioning
confidence: 99%